log7x+log(x+1)−log7=log2x−logx \log7x+\log(x+1)-\log7=\log2x-\log x log7x+log(x+1)−log7=log2x−logx
?=x ?=x ?=x
Defined domain
x>0
x+1>0
x>-1
log7x+log(x+1)−log7=log2x−logx \log7x+\log\left(x+1\right)-\log7=\log2x-\log x log7x+log(x+1)−log7=log2x−logx
log7x⋅(x+1)7=log2xx \log\frac{7x\cdot\left(x+1\right)}{7}=\log\frac{2x}{x} log77x⋅(x+1)=logx2x
We reduce by: 7 7 7 and by X X X
x(x+1)=2 x\left(x+1\right)=2 x(x+1)=2
x2+x−2=0 x^2+x-2=0 x2+x−2=0
(x+2)(x−1)=0 \left(x+2\right)\left(x-1\right)=0 (x+2)(x−1)=0
x+2=0 x+2=0 x+2=0
x=−2 x=-2 x=−2
Undefined domain x>0
x−1=0 x-1=0 x−1=0
x=1 x=1 x=1
1 1 1